PERKEMBANGAN ISLAM DI KOREA SELATAN - Wulandari Nurul Utami (Hadharah: Jurnal Keislaman dan Peradaban, 2023)
This paper aims to describe the development of Islam in one of the East Asian Islamic minority countries, South Korea. The method used in this paper is the historical method with four stages of heuristics, source criticism, interpretation and historiography. This paper describes the dynamics of the development of Islam in South Korea from the time of the three dynasties, namely the Silla Dynasty, the Goryeo Dynasty, and the Joseon Dynasty to contemporary times. Today, Islam is still an unfamiliar religion to South Korean society, especially after the WTC bombing, the bad view created against Islam also affects South Korean society with several acts of discrimination experienced by Muslims in South Korea. It is concluded that although South Korea is an Islamic minority country with several acts of discrimination against Muslims, but slowly Islam began to show its existence in the gingseng-producing country.